2004
DOI: 10.1029/2004gl019702
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol radiative forcing over a tropical urban site in India

Abstract: Using collocated measurements of aerosol radiative properties and radiative fluxes, aerosol radiative forcing is estimated at a tropical urban site in India, located between the sub‐continent and the Indian Ocean Experiment [INDOEX] sites. Observed sun/sky radiance data are used to derive aerosol spectral optical depth, single scattering albedo [SSA], asymmetry parameter, precipitable water and total column ozone. These serve as inputs to a radiative transfer model, to estimate aerosol forcing at the surface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Minor differences can be seen in estimated forcing values between the present study and the previous one by Pandithurai et al (2004). In order to ascertain the differences, we performed an exercise for the same months (November to April) by putting the uniform albedo value (0.15), as the case with previous study, in the model instead of wavelength dependence of albedo and found that the present values fall short by 9% and 85% at surface and TOA levels, respectively.…”
Section: Comparison and Implications To Regional Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Minor differences can be seen in estimated forcing values between the present study and the previous one by Pandithurai et al (2004). In order to ascertain the differences, we performed an exercise for the same months (November to April) by putting the uniform albedo value (0.15), as the case with previous study, in the model instead of wavelength dependence of albedo and found that the present values fall short by 9% and 85% at surface and TOA levels, respectively.…”
Section: Comparison and Implications To Regional Climatementioning
confidence: 99%
“…By definition, the aerosol direct short-wave (solar) radiative forcing (ADRF) is the change (DF) in the radiation flux (F) either at the surface (S) or at the TOA, respectively without and with the aerosol particles in the atmosphere (Russell et al, 1999;Podgorny et al, 2000;Yu et al, 2001;Pandithurai et al, 2004). This is generally represented as:…”
Section: Aerosol Radiative Forcingmentioning
confidence: 99%
“…Such effects are produced by the optical, chemical and microphysical properties of the aerosols, nature of the underlying surface, cloudiness etc. (Babu et al 2002;Pandithurai et al 2004). The ARF is given by the expression:…”
Section: Role Of Aerosols On the Dynamical Responsementioning
confidence: 99%
“…Similarly, in the north Indian region also there are some studies on aerosol characterization and forcing but they are limited to pre-monsoon season only (Singh et al, 2005;Pandithurai et al, 2008;Beegum et al, 2008). Present study, for the first time, is focused on the monthly variation of clear sky direct aerosol radiation forcing (DARF) over a north Indian station, Delhi, for the whole year during January 2006 to January 2007.…”
Section: Introductionmentioning
confidence: 99%